Development of Streptococcus pneumoniae Pan‐Group Quorum‐Sensing Modulators. (15th October 2019) - Koirala, Bimal; Tal‐Gan, Yftah
Abstract: The rapid increase in multidrug‐resistant pathogens is a major health concern that could bring mankind back to the pre‐antibiotic era. Streptococcus pneumoniae is a highly recombinogenic opportunistic pathogen that causes a variety of deadly diseases and rapidly develops resistance to current antibiotic treatments. S. pneumoniae pathogenicity is dependent on a cell‐density communication mechanism, or quorum sensing (QS), termed the competence regulon. In this work, we set out to design signal‐based QS modulators capable of affecting the two specificity groups found in S. pneumoniae . Through systematic analysis and rational design, we were able to construct peptide‐based pan‐group QS activators and inhibitors with activities in the nanomolar range. These novel analogues are privileged scaffolds for the development of anti‐virulence therapeutics against S. pneumoniae infections. Abstract : The best of both worlds : We sought to identify pan‐group modulators of the S. pneumoniae competence quorum‐sensing (QS) circuitry by systematically altering the competence‐stimulating peptide (CSP) 2 scaffold with the residues present in CSP1. The approach was to merge these two CSPs into a hybrid sequence that allows identification of a pan‐group QS inhibitor with activities in the nanomolar range.